Isolasi dan Karakterisasi Bakteri Asam Laktat (BAL) pada Fermentasi Durian Montong (Durio zibethinus Murr.) - Viona, Alda; Fevria, Resti; Irdawati, Irdawati; Putri, Dwi Hilda (Lembaga Yasin AlSys, 2024)
Lactic acid bacteria is a group of bacteria that produce lactic acid as the main product in fermentation. Tempoyak is a processed durian fruit product made by anaerobic spontaneous fermentation for 3-7 days. The fermentation process that occurs in making tempoyak is lactic acid fermentation. Carbohydrates are broken down into glucose, then BAL will ferment the glucose to produce lactic acid (main product), ethanol and CO2 (by-product). The aim of this research was to isolate lactic acid bacteria (LAB) from fermented durian. This research method is descriptive. 8 BAL isolates were obtained and identified macroscopically and microscopically by gram staining method. Based on the research that has been done, colonies of gram-positive bacteria in the form of bacilli and coccus cells were obtained. Gram-positive bacteria have cell wall characteristics with thicker peptidoglycan so that color absorption from violet crystals absorbed in cells will survive.